Smart health records - Lestari V.N.S.; Rahim R.; Nguyen P.T.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
If there is no health record history of a patient then it will be very difficult for treating in different hospitals. Especially for travelers and in the case of emergency it can ruin the auspicious treatment and diagnosis. If the smart health records are based on Cloud then there is higher difficulties for protection and security, the open difficulties of interoperability and joining and also lack of every day support for the high accessibility of wellbeing history. The smart health records that are already exists can store only limited about of data of patients and they stored data only for specific hospital and do not support versatility of patients crosswise over various medical clinics. The technology that use better treatment for patients, improve quality of life for everyone and provide better diagnostic tools can be consider as smart health. BEIESP.